(untitled) (International Educators Conference, 2025)
This article analyzes the pedagogical opportunities of personalizing the educational process using artificial intelligence (AI). Based on international and national research, the role of AI technologies in effectively organizing the learning process, tailoring it to individual needs and abilities, and optimizing teachers’ activities is highlighted. Additionally, existing challenges and recommendations for addressing them are proposed.